The Romance of Real Life Charles Brockden Brown and the Origins of American Culture - Watts, Steven (Johns Hopkins University Press, 2019)
Originally published in 1994. The Romance of Real Life aims to reconstruct historically the life and writings of Charles Brockden Brown in terms of their cultural connection. Watts examines in detail Brown's early and later writings. By looking at these often-neglected works more closely, he offers a new perspective on the well-known novels from the late 1790s. Watts's synthetic look at genre as well as chronology reveals broader connections between Brown's literature and American society and culture in the decades of the early republic. Furthermore, Watts situates Brown's writings in terms of the interplay of text, context, and the self, with each factor recognized as mutually shaping the others. The Romance of Real Life incorporates sensitivity to the "social history of ideas," in which both the form and content of language remain rooted in the material experience of real life.